Analysis of distribution in the human, pig, and rat genomes points toward a general subtelomeric origin of minisatellite structures. - Amarger, V; Gauguier, D; Yerle, M; Apiou, F; Pinton, P; Giraudeau, F; Monfouilloux, S; Lathrop, M; Dutrillaux, B; Buard, J; Vergnaud, G (1998)
We have developed approaches for the cloning of minisatellites from total genomic libraries and applied these approaches to the human, rat, and pig genomes. The chromosomal distribution of minisatellites in the three genomes is strikingly different, with clustering at chromosome ends in human, a seemingly almost even distribution in rat, and an intermediate situation in pig. A closer analysis, however, reveals that interstitial sites in pig and rat often correspond to terminal cytogenetic bands in human. This observation suggests that minisatellites are created toward chromosome ends and their internalization represents secondary events resulting from rearrangements involving chromosome ends.